Socioeconomic Indicators for the Evaluation of Forest Sustainability in Northern Uruguay - Irisity, Fernando; Chiappe, Marta (Agrociencia Uruguay, 2012)
The objective of this work was to validate the social and economic indicators of the Montréal Process and to identify additional indicators relevant to assess forest sustainability in the Departments of Tacuarembó and Rivera, Uruguay. First, it was necessary to know the peculiarities of the region and types of enterprises, in order to define the stakeholders to be involved in the assessment. Then, qualified persons suitable for interviewing were identified, who in turn referred to others, according to the «snowball sampling» technique. Thirty regional stakeholders of the forest business were queried. They were asked on the relevance of socio-economic indicators, as defined in the Montréal Process. Agreement over the relevance to include the indicator «Employment and community needs» was 100%, and only 3% endorsed the indicator «Recreation and tourism» as necessary. Additionally, the need to include some additional indicators, which would assess «employment quality», «how local communities are affected by forests» and «how landscape is affected» came up.